A STUDY OF MICROTREMOR HVSR IN THE RIO-ANTIRIO AREA, (GREECE) - Norda, M.E.; Prapiga, A.; Paraskevopoulos, P.; Tselentis, G.A (Bulletin of the Geological Society of Greece, 2016)
Horizontal to Vertical Spectral Ratio (HVSR) method has been applied on ambient noise records at the Rio- Antirio area (central Greece). The dataset used was recorded during 7 days by 12 temporary seismic stations deployed in the area. The stations were laid out along a profile and their interval was approximately 500m. The main part of the processing was done using Geopsy software. The aim of this study was to estimate the fundamental frequency at the station sites and its variation with time and azimuth. The processing results showed that for most stations along the profile, the peaks of the HVSR curve are not strong enough and often there are, more than one, peaks, which seem to be persistent during the whole recording time. When taking the azimuth into account, some of the stations show dominant and persistent directions were the HVSR ratio is stronger, while it has been observed that this direction could vary for different frequency peaks of the same stations. Finally, the top sediment layer’s geometry and thickness were estimated using Vs velocity results from nearby crosshole measurements.